2013
DOI: 10.1016/j.antiviral.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral resistance among highly pathogenic influenza A (H5N1) viruses isolated worldwide in 2002–2012 shows need for continued monitoring

Abstract: Highly pathogenic (HP) H5N1 influenza viruses are evolving pathogens with the potential to cause sustained human-to-human transmission and pandemic virus spread. Specific antiviral drugs can play an important role in the early stages of a pandemic, but the emergence of drug-resistant variants can limit control options. The available data on the susceptibility of HP H5N1 influenza viruses to neuraminidase (NA) inhibitors and adamantanes is scarce, and there is no extensive analysis. Here, we systematically exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 53 publications
1
75
0
Order By: Relevance
“…These results, along with others, have contributed to an increased focus on the development of intervention strategies with the ability to modulate deleterious host immune responses, such as those triggered by ROS, in an attempt to ameliorate disease severity (9). This is particularly important given the documentation of H5N1 and H7N9 influenza virus antiviral drug resistance (2,13). The data presented here provide important mechanistic evidence to suggest that apocynin or its derivatives could be used therapeutically to reduce immunopathology following H5N1 or H7N9 avian virus infection, resulting in amelioration of disease severity.…”
Section: ␤ [Mip-1␤] Interleukin-6 [Il-6] Interferon Alpha [Ifn-␣]mentioning
confidence: 99%
“…These results, along with others, have contributed to an increased focus on the development of intervention strategies with the ability to modulate deleterious host immune responses, such as those triggered by ROS, in an attempt to ameliorate disease severity (9). This is particularly important given the documentation of H5N1 and H7N9 influenza virus antiviral drug resistance (2,13). The data presented here provide important mechanistic evidence to suggest that apocynin or its derivatives could be used therapeutically to reduce immunopathology following H5N1 or H7N9 avian virus infection, resulting in amelioration of disease severity.…”
Section: ␤ [Mip-1␤] Interleukin-6 [Il-6] Interferon Alpha [Ifn-␣]mentioning
confidence: 99%
“…Two FDA-approved adamantane-based drugs, amantadine and rimantadine (2,8), are potent M2 inhibitors that can neutralize influenza virus in humans and other animals. However, the emergence of widespread highly virulent adamantane-resistant strains such as avian and swine influenza virus strains (9,10) has prompted the need for newer antivirals. Drug discovery efforts targeting M2 have been difficult due to the toxicity of M2 in cells (11), the difficulty of reconstituting M2 in liposomes for largescale application (12,13), and the labor-intensive, low-throughput electrophysiological approaches typically used to study ion channels.…”
mentioning
confidence: 99%
“…The analysis of predicted amino acid sequence for the NA of Dk/VN/QB1207/12 and representative Vietnamese strains did not identify any of the amino acid substitutions known to relate to the oseltamivir resistance (Table 4) [35,36]. In the M2 protein of Dk/VN/QB1207/12, the S31A mutation known to be involved in amantadine resistance was also not seen.…”
Section: Genetic Analysismentioning
confidence: 98%
“…However, the M2 of Dk/VN/QB1207/12 contained an amino acid substitution at position 27 (V27I), which may suggest a reduced susceptibility to amantadine (Table 4) [37,38]. Recently, Govorkova et al [36] systematically examined the prevalence of NA inhibitor and amantadine resistance among the HPAIVs circulating worldwide, and reported that most of the HPAIVs are likely to be susceptible to NA inhibitors while some proportion will also be susceptible to amantadine. The genetic features of Dk/VN/QB1207/12 seem to match that prediction.…”
Section: Genetic Analysismentioning
confidence: 99%